ANALiSIS NILAI EFISIENSI PERBANKAN DI INDONESIA MENGGUNAKAN METODE DATA ENVELOPMENT ANALYSIS (DEA) (Studi Pada Bank Umum Konvensional yang Terdaftar di BEI periode 2011-2014) - Astutiningrum, Lestari Puji; Haryanto, A. Mulyo (Faculty of Economics and Business Diponegoro University, 2016)
Capital buffer is the difference between the bank's capital ratios with a minimum capital adequacy ratio of the central bank imposed . Capital buffers can be used by banks as capital reserves in the event of economic shocks that are not profitable.Committees of international banks (Basel Committee on Banking Supervision) implemented an kesepekatan (Basel Accord), which requires that each bank has a capital reserve (CAR) of 13% in order to strengthen its capital position , reduce inequality on different regulations in each country , and consider the various banking risks international banking in order to realize a healthy and stable .Efficiency is closely linked with the capital buffer. Simply put Efficiency can be measured by using ROA and BOPO. In this research the efficiency is measured by the non -parametric methods make use of Data Envelopment Analysis (DEA) using three input variables , namely the Third Party Funds (DPK), labor costs and other operating costs as well as using a variable output that is lending.The research was conducted on BUMN Banks and non BUMN Bank in Indonesia in 2011-2014. The results of this study showed no difference between the efficiency of state-owned bank and non- bank state-owned enterprises. While capital buffer has no effect on the value of banking efficiency.